Community-Based Needs Assessment of Neurodevelopment, Caregiver, and Home Environment Factors in Young Children Affected by HIV in Lima, Peru. (March 2017) - Muñoz, Maribel; Nelson, Adrianne; Johnson, Maureen; Godoy, Nancy; Serrano, Esther; Chagua, Engerid; Valdivia, Jesica; Santacruz, Janeth; Wong, Milagros; Kolevic, Lenka; Kammerer, Betsy; Vega, Clemente; et al.
Background: In many resource-poor settings such as Peru, children affected by HIV have a high prevalence of neurodevelopmental delays (NDDs) and remain excluded from adequate treatment. Methods: Community health workers (CHWs) administered NDD screening instruments to assess child development and associated caregiver and household factors in 14 HIV-affected parent–child dyads. Focus group discussion with caregivers was conducted to explore their needs and behaviors around early child stimulation and to assess their perceptions of the screening experience. Results: Over 70% of the children had abnormal classification in at least 1 (out of 5) developmental domains according to Ages and States Questionnaire–provided cutoff scores. Caregiver depression and stress were associated with abnormal development as were some parenting behavior factors. Knowledge about child development was low. Caregivers felt testing and discussing results with a CHW were very insightful. Reported caregiver behavior differed between caregivers with HIV-infected children and those with uninfected children. Conclusion: Taken together, these exploratory quantitative data suggest that parenting behaviors associated with low child development scores may be modifiable and that community-based testing is well received and informative to these HIV-infected caregivers.